Assessment of Genetic Stability Among Micropropagated Prunus dulcis Plantlets Using SCoT Markers in Duhok Province Kurdistan Region/Iraq - Diana SALEH; Jaladet JUBRAEL; Mosleh SALEH DUHOKY (Bulletin of University of Agricultural Sciences and Veterinary Medicine Cluj-Napoca: Horticulture)
The novel DNA marker technique, namely Start Codon Targeted (SCoT), was used to assess genetic stability of in vitro raised plants of Prunus dulcis. The plantlets were produced by the multiplication of axillary buds and from callus regeneration. Within the experiment, eight different almond genotypes, collected from different parts of Duhok Provence, considered as mother plants, as well as their 16 micropropagated plantlets, were subjected to molecular analysis, using 15 primers of SCoT Polymerase Chain Reaction markers for all 24 samples. A high degree of polymorphism was detected among the plantlets obtained both from the buds and from the indirect callus regeneration, revealing a vast array of genetic changes compared to the mother plants. The results of DNA banding patterns between the eight almond mother plants produced a total of 181 reproducible and scorable bands, out of which 169 bands were polymorphic, leading to a rate of polymorphism ranging 72.7 to 100 %. The results of this study evidenced that SCoT markers are reliable for genetic stability analysis of Prunus dulcis and may suggest their application in the commercial micropropagation for detection of true-to-type to mother plants plantlets.